Effects of taurine supplementation on productive performance, nutrient digestibility and gene expression of nutrient transporters in quails reared under heat stress - Orhan, Cemal; Küçük, Ömersman; Şahin, Nurhan; Tuzcu, Mehmet; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2020)
This study was conducted to examine the effects of dietary taurine supplementation on productive performance, nutrient digestibility, antioxidant status, and the gene expression of ileal nutrient transporters in laying quails reared under heat stress (HS). One hundred and eighty laying Japanese quails (Coturnix coturnbc japonica) were fed a basal diet or basal diet supplemented with either 2.5 or 5 g of taurine per kg of diet, and reared at either 22 +/- 2 degrees C for 24 h/d (thermoneutral, TN) or 34 +/- 2 degrees C for 8 h/d (HS) for 12 weeks. The quails reared under HS consumed less feed, produced less egg, and had lower dry matter, organic matter and crude protein apparent digestibilities compared with the quails reared under the TN condition (P = 0.001). However, increasing taurine concentrations in the diet improved feed intake and egg production (P = 0.001), but also the apparent digestibilities (P <= 0.027) in quails reared under HS. The greater doses (5 g/kg) of taurine resulted in more responses. The quails reared under HS had greater serum and liver MDA concentrations (P = 0.0001) which decreased with dietary taurine supplementations, particularly greater doses. The gene expressions of ileal PEPT1, EAAT3, CAT1, CAT2, SGLT1, SGLT5, GLUT2, and GLUTS decreased under HS conditions (P = 0.001). However, supplementing taurine, in a dose-dependent fashion, to the diet of quails reared under HS resulted in increases in the gene expressions of the transporters (P < 0.05) except for CAT1. The results of the present work showed that taurine supplementation, particularly with greater doses (5 g/kg), to the diet of laying quails kept under HS acts as alleviating negative effects of HS, resulting in improvements in productive performance and nutrient digestion, and also upregulation of ileal nutrient transporters.
Keywords: Taurine; Antioxidant status; Digestibility; Nutrient transporters; Quail